Chromatin structure influences the sensitivity of DNA to gamma-radiation - Falk, Martin; Lukášová, Emilie; Kozubek, Stanislav (Biochimica et biophysica acta, 2008)
For the first time, DNA double-strand breaks (DSBs) were directly visualized in functionally and structurally different chromatin domains of human cells. The results show that genetically inactive condensed chromatin is much less susceptible to DSB induction by gamma-rays than expressed, decondensed domains. Higher sensitivity of open chromatin for DNA damage was accompanied by more efficient DSB repair. These findings follow from comparing DSB induction and repair in two 11 Mbp-long chromatin regions, one with clusters of highly expressed genes and the other, gene-poor, containing mainly genes having only low transcriptional activity. The same conclusions result from experiments with whole chromosome territories, differing in gene density and consequently in chromatin condensation. It follows from our further results that this lower sensitivity of DNA to the damage by ionizing radiation in heterochromatin is not caused by the simple chromatin condensation but very probably by the presence of a higher amount of proteins compared to genetically active and decondensed chromatin. In addition, our results show that some agents potentially used for cell killing in cancer therapy (TSA, hypotonic and hypertonic) influence cell survival of irradiated cells via changes in chromatin structure and efficiency of DSB repair in different ways.
Keywords: buněčné jádro; Gamma Rays; Humans; hybridizace in situ fluorescenční; Chromatin; G1 fáze; kůže; Cell Nucleus; Histone Deacetylase Inhibitors; Fluorescent Antibody Technique; In Situ Hybridization, Fluorescence; histondeacetylasy; regulace genové exprese; Gene Expression Regulation; apoptóza; Hydroxamic Acids; Skin; poškození DNA; inhibitory enzymů; inhibitory histondeacetylas; DNA Damage; S Phase; Chromatin Immunoprecipitation; záření gama; S fáze; Cobalt Radioisotopes; G1 Phase; chromatin; DNA; Histone Deacetylases; lidé; chromatinová imunoprecipitace; DNA Repair; oprava DNA; fluorescenční protilátková technika; fibroblasty; Enzyme Inhibitors; Fibroblasts; Apoptosis; kyseliny hydroxamové; radioizotopy kobaltu